2019
DOI: 10.1111/cpr.12567
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: miR‐664a‐3p functions as an oncogene by targeting Hippo pathway in the development of gastric cancer

Abstract: Objectives: It has been accounted that miR-664a-3p has different functions in several malignancies; however, the precise role and underlying mechanism in gastric cancer have not been elucidated. Our study aims to explore the function of miR-664a-3p on the progression of gastric cancer (GC).Methods: qRT-PCR was applied to detect the expression of miR-664a-3p in GC tissues and cells. The functions of miR-664a-3p on GC in vitro were examined by cell proliferation assay, and transwell assay. Related proteins of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…To determine whether HPSE2 could reverse the oncogenic effects of miR-15b-5p, we co-transfected breast cancer cells with miR-15b-5p inhibitor and HPSE2 siRNA according to the experimental design from previous reported (22)(23)(24). The mRNA and protein levels of HPSE2 are shown in Figures 7A,B.…”
Section: Hpse2 Attenuates the Function Of Mir-15b-5p In Bc Cellsmentioning
confidence: 99%
“…To determine whether HPSE2 could reverse the oncogenic effects of miR-15b-5p, we co-transfected breast cancer cells with miR-15b-5p inhibitor and HPSE2 siRNA according to the experimental design from previous reported (22)(23)(24). The mRNA and protein levels of HPSE2 are shown in Figures 7A,B.…”
Section: Hpse2 Attenuates the Function Of Mir-15b-5p In Bc Cellsmentioning
confidence: 99%
“…In recent years, continuous researches have been carried out to improve the prognosis of patients with advanced GC. Although considerable improvements have been achieved in understanding developmental mechanisms and therapeutic strategies [2,3], patients with advanced GC still have poor prognosis. The 5-year overall survival rate of patients with GC remains quite low at approximately 25% [4,5].…”
Section: Introductionmentioning
confidence: 99%
“… 1 The understanding of the pathogenesis of colorectal cancer has improved with advances made in the discovery of new oncogenes and anti-oncogenes. 18 - 20 Despite these advances, the underlying mechanism of these diseases remains largely unknown. Recent evidence has shown that snoRNAs play an important regulatory role in the occurrence and development of various diseases, especially cancer.…”
Section: Discussionmentioning
confidence: 99%